Microstructure‐ and Theory‐Based Modeling and Simulation of Batteries and Fuel Cells. Issue 6 (17th April 2019) - Latz, Arnulf; Danner, Timo; Horstmann, Birger; Jahnke, Thomas
Abstract: The quality of digitalized design and development processes for advanced electrochemical technologies depends crucially on the accuracy of available models and the level of details at which simulations can be performed. In this article, an overview is given over recent advances in developing coupled models of transport and electrochemistry and simulation tools to investigate and modify very detailed processes in batteries and fuel cells, two of the decisive electrochemical technologies for future energy markets. Abstract : An overview over new predictive modeling and simulation techniques for batteries and fuel cells will be given. A special focus is on microstructure resolved simulations for Li‐ion batteries, advanced modeling techniques for new electrolytes and metal air batteries and spatially resolved simulations of low temperature (PEM) fuel cells.